General practice‐recorded depression and antidepressant use in young people with newly diagnosed Type 1 diabetes: a cohort study using the Clinical Practice Research Datalink. Issue 2 (21st October 2013) - Morgan, E.; Patterson, C. C.; Cardwell, C. R.
Abstract Aims To investigate whether young people with Type 1 diabetes have an increased rate of depression and antidepressant use and whether their risk varies by age group, time from diabetes diagnosis, calendar period of diagnosis or complications status. Methods A cohort of incident cases of patients with Type 1 diabetes diagnosed before 35 years of age (n = 5548) was identified within the Clinical Practice Research Datalink and individually age and sex matched with up to two control subjects without diabetes (n = 10 657). Patients with depression were identified through general practice‐recorded depression codes and antidepressant prescriptions. Cox regression models gave hazard ratios for depression in people with Type 1 diabetes compared with control subjects. Results People with Type 1 diabetes were twice as likely to have a record of antidepressant use and general practice‐diagnosed depression as their matched control subjects (hazard ratio 2.08, 95% CI 1.73–2.50, P < 0.001). These associations varied by time from diagnosis, with marked increases observed within the first 5 years of diagnosis (hazard ratio 2.14, 95% CI 1.51–3.03, P < 0.001), and by age at diabetes diagnosis, with excesses noted even in the 10‐ to 19‐year age group (hazard ratio 1.45, 95% CI 1.06–1.98, P = 0.02). Conclusions This population‐based study shows that people with Type 1 diabetes have higher rates of general practice‐recorded depression and antidepressant use. The excess is present within 5 years of diabetes diagnosis, suggesting psychological input for patients is warranted in the early years of their condition.